К вопросу определения граничных условий теплообмена для расчетного уточнения возможности продления срока эксплуатации корпусных деталей и роторов паровых турбин - Черноусенко, Ольга Юрьевна (Национальный технический университет "Харьковский политехнический институт", 2006)
Наведено опис методики розрахункового визначення граничних умов теплообміну для уточнення можливості продовження терміну експлуатації корпусів і роторів парових турбін великої потужності, а також удосконалення на базі таких оцінок систем діагностики технічного стану парових турбін.

It is brought description over of method of calculation determination of scope terms of heat exchange for clarification of possibility of extension of term of exploitation of corps and rotors of steam-turbines of large power, and also improvement on the base of such estimations of the systems of diagnostics of the technical state of steam-turbines.
To the question of boundary conditions determination of heat transfer for calculated of improvement of the opportunity prolongation term exploitation of case details and of rotors of the steam turbines
Keywords: регулирующий клапан; КПД; энергоблок; планово-предупредительный ремонт; АСКТД; высокотемпературный цилиндр; температура пара; стопорный клапан